2016
DOI: 10.1155/2016/3068467
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Flow Sevoflurane Anesthesia on Pulmonary Functions in Patients Undergoing Laparoscopic Abdominal Surgery

Abstract: Objective. The aim of this prospective, randomized study was to investigate the effects of low-flow sevoflurane anesthesia on the pulmonary functions in patients undergoing laparoscopic cholecystectomy. Methods. Sixty American Society of Anesthesiologists (ASA) physical status classes I and II patients scheduled for elective laparoscopic cholecystectomy were included in the study. Patients were randomly allocated to two study groups: high-flow sevoflurane anesthesia group (Group H, n = 30) and low-flow sevoflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
1
12
1
Order By: Relevance
“…One study demonstrated that the low flow anaesthesia technique is a safer technique compared to the high flow anaesthesia technique in pulmonary fever in healthy adult patients. 16 Later studies showed no difference in outcome from pediatric patients under anaesthesia and maintained its anaesthesia condition.…”
Section: Low Flow Anaesthesiamentioning
confidence: 99%
“…One study demonstrated that the low flow anaesthesia technique is a safer technique compared to the high flow anaesthesia technique in pulmonary fever in healthy adult patients. 16 Later studies showed no difference in outcome from pediatric patients under anaesthesia and maintained its anaesthesia condition.…”
Section: Low Flow Anaesthesiamentioning
confidence: 99%
“…These contradictory findings between the results of our study and Bilgi et al [4] might have occurred because the mean duration of surgery was longer in the latter. Doger et al [10] investigated the effects of low-flow (1 L/min) and high-flow (4 L/min) sevoflurane anesthesia on pulmonary functions. FVC, FEV1, and FEV1/FVC% were measured while the patients were in the sitting position.…”
Section: Discussionmentioning
confidence: 99%
“…This means that if minimal-flow anesthesia is successfully used in a patient, it will never cause changes in pulmonary functions compared to highflow anesthesia. The minimal-flow anesthesia method normally affects only the amount of waste gas [10]. However, possible disadvantages that may arise from the improper use of minimal-flow anesthesia include hypoxia, excessive or insufficient concentrations of volatile substances, hypercapnia, and the accumulation of potentially toxic gases.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies gave mixed or controversial results regarding the effects of high-flow and low-flow on pulmonary functions postoperatively. [ 4 5 ] Previous studies have validated the use of spirometry in assessing lung functions in terms of FVC and FEV1. Even in the presence of atelectasis,[ 6 ] the spo2 was maintained between the high-flow and low-flow groups indicating that the available alveolar exchange is sufficient to maintain oxygenation.…”
Section: Introductionmentioning
confidence: 99%